Implementasi Implementasi Alat Pembakaran Minim Asap untuk Pengelolaan Sampah Rumah Tangga di Desa Wangunsari - Aryanto, Anton; Pratama, Muhamad Wanda; Lyle, Julian; Rayhan, Ayu Putri; Setiawan, Kiki; Noor, Jalaludin Mahmud; Ridwan, Muhammad; Choer, Yayan Miftahul; Pravitasari, Filly (Universitas Insan Cendekia Mandiri, 2026)
This community service program aims to address the accumulation of dry waste in Cijengkol Hamlet, Wangunsari Village, through the implementation of a low-smoke waste-burning stove as an appropriate technology. A participatory method was applied, including needs assessment, focus group discussions, device design, and field trials with residents. The results indicate that the stove reduced visible smoke by approximately 60%, accelerated combustion, and decreased ash residue. Community participation increased, as indicated by resident involvement and a reduction of dry waste by approximately 35% within three weeks. The program contributed to improved waste management behavior and enhanced local capacity for independent waste handling. Overall, the technology proved effective and applicable for rural areas facing similar challenges.